Florida's Introduced Birds: Muscovy Duck (Cairina moschata) - Steve A. Johnson; Michelle Hawk (EDIS)
WEC-254, a 4-page illustrated fact sheet by Steve A. Johnson and Michelle Hawk, introduces the muscovy duck — species description, similar species, native range and habitats, mode of introduction, introduced range and habitats, ecology, ecological impacts, impacts to people and pets, solutions, and how readers can help. Includes references. Published by the UF Department of Wildlife Ecology and Conservation, March 2009.